Ionospheric Gradient Threat Mitigation in Future Dual Frequency GBAS - Michael Felux; Mihaela-Simona Circiu; Jiyun Lee; Florian Holzapfel (International Journal of Aerospace Engineering)
The Ground Based Augmentation System (GBAS) is a landing system for aircraft based on differential corrections for the signals of Global Navigation Satellite Systems (GNSS), such as GPS or Galileo. The main impact on the availability of current single frequency systems results from the necessary protection against ionospheric gradients. With the introduction of Galileo and the latest generation of GPS satellites, a second frequency is available for aeronautical navigation. Dual frequency methods allow forming of ionospheric free combinations of the signals, eliminating a large part of the ionospheric threats to GBAS. However, the combination of several signals increases the noise in the position solution and in the calculation of error bounds. We, therefore, developed a method to base positioning algorithms on single frequency measurements and use the second frequency only for monitoring purposes. In this paper, we describe a detailed derivation of the monitoring scheme and discuss its implications for the use in an aviation context.